2013
DOI: 10.1186/alzrt182
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive behavioral characterization of an APP/PS-1 double knock-in mouse model of Alzheimer's disease

Abstract: IntroductionDespite the extensive mechanistic and pathological characterization of the amyloid precursor protein (APP)/presenilin-1 (PS-1) knock-in mouse model of Alzheimer's disease (AD), very little is known about the AD-relevant behavioral deficits in this model. Characterization of the baseline behavioral performance in a variety of functional tasks and identification of the temporal onset of behavioral impairments are important to provide a foundation for future preclinical testing of AD therapeutics. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 141 publications
16
101
1
Order By: Relevance
“…Although our MWM data from the probe trial show improved performance for the distance traveled to the position where the platform had been located, there were no significant differences for latency time to platform. Results of the training trials showed a general improvement for BNC-1 treated mice although there was considerable variability among the mice which is consistent with recent studies that suggest the MWM may not be as effective as other tests (novel object recognition and radial arm maze) at the detection of behavioral deficits in APP/PS1 mice [54]. We are planning to use the alternative behavioral tests to characterize animals currently on a diet containing BNC-1.…”
Section: Discussionsupporting
confidence: 79%
“…Although our MWM data from the probe trial show improved performance for the distance traveled to the position where the platform had been located, there were no significant differences for latency time to platform. Results of the training trials showed a general improvement for BNC-1 treated mice although there was considerable variability among the mice which is consistent with recent studies that suggest the MWM may not be as effective as other tests (novel object recognition and radial arm maze) at the detection of behavioral deficits in APP/PS1 mice [54]. We are planning to use the alternative behavioral tests to characterize animals currently on a diet containing BNC-1.…”
Section: Discussionsupporting
confidence: 79%
“…The open field and elevated plus maze test confirmed that anxietylike behaviors continue to exist in the late stages of this mouse AD model, similar to the Tg2576 (Gil-Bea et al 2007;Lassalle et al 2008), J20 (Harris et al 2010;Cissé et al 2011), and 5xFAD mice (Wirths et al 2010;Shukla et al 2013), all of which also exhibit anxietyrelated behavior deficits in the elevated plus maze task. However, there is no anxiety-related behavior abnormality in the APP/PS1 double knock-in mice from 7 to 24 months old (Webster et al 2013); while 3xFAD mice show decreased anxiety-related behavior in the open field and elevated plus maze test (Nelson et al 2007;Filali et al 2012). The variability of anxiety-related behavior in these commonly used AD mouse models supports a heterogeneous range of noncognitive symptoms caused by Aβ-related pathogenesis.…”
Section: Discussionmentioning
confidence: 91%
“…The elevated plus maze test was utilized to assess anxiety-related behavior in response to a potentially dangerous environment (Webster et al 2013). The maze consists of two enclosed arms (50 × 10 × 40 cm), two open arms (50 × 10 cm), and center area (10 × 10 cm) elevated 100 cm above the floor.…”
Section: Elevated Plus Mazementioning
confidence: 99%
“…The group of Morgan also showed that RAWM was impaired starting at about 15 months of age in both APP and APP/PS1(line 5.1) mice, whereas they learned and remembered the platform location at 6 and 11.5 months of age [230, 231]. Recently, Webster et al [232] have studied RAWM in four different age groups (7, 11, 15, and 24 months) in APP/PS1 knock-in mice characterized by the introduction of a Swedish FAD K670N/M671L point mutations, the humanization of the mouse β-amyloid sequence, and the introduction of a P264L mutation in the PS1 gene. These mice performed worse than WT controls in the RAWM task starting at 15 months of age, and the increase of errors paralleled the increase of age and the disease progression.…”
Section: Behavioral Studiesmentioning
confidence: 99%